Quote Originally Posted by tpoma View Post
Just want to double check that I am doing these right. Not looking for an answer.

5p^4q - 20q^3 should = 5pq(p^3-4q^2) right?

72x^2 - 2y^2 should = (2y-3x) (2y-36x) right?

Thanks so much!
The first one

$\displaystyle 5p^4q - 20q^3 = 5q(p^4 - 4q^2)$ as mentioned above. But this can be factorised further.

$\displaystyle 5p^4q - 20q^3 = 5q(p^4 - 4q^2)$

$\displaystyle = 5q[(p^2)^2 - (2q)^2]$

$\displaystyle = 5q(p^2 + 2q)(p^2 - 2q)$

using the Difference of Two Squares rule.